Configuração, desconstrução e reconfiguração: Cristóvão Colombo na literatura americana - Machado, Douglas William (2014)
The present research aims to produce a comparative reading of Columbia (1892), written by John Musick, Los perros del Paraíso (1989), by the Argentinean Abel Posse and A Caravela dos insensatos: uma viagem pela renascença (2006), by the Brazilian Paulo Novaes to expose the characterization of Christopher Columbus' figure in American Literature as a hero on the discovery of America, as well as its deconstruction and its subsequent reconfiguration. The novels in which this comparison was carried out are part of the fictional hybrid genre called historical novel. The first one, written in North America, is a traditional historical novel and it reveals Columbus as a mythical hero of the New World. The second one, written inside the Spanish American context, is a new Latin American historical novel that presents processes of deconstruction of the existing historical speech and gives visibility to the Latin American people so that they are able to make a new reading on their own past. However, the third one, written more recently in our country, brings back the traditional historical novel model and reconfigures Christopher Columbus' traditional heroic-mythical image. Therefore, this novel ignores the voice of the Latin American people and all the critical and deconstructionist production of the Spanish American Literature done along the 20th century, which was based upon deconstructionist resources like parody, carnivalization, intertextuality, anachronies, irony, multiperspectivism and much more. These writings are constantly questioning power relations, control of truth and also deconstruct speeches that had been shaping Latin American s identity. Thus, our research aims to explain the relationship between American and the old European metropolis: colonization, decolonization and maintenance of certain aspects from the colonizatory dependence of America. These processes are reinforced by literary creations; whether they are critical as the new historical novel or traditional, still appealing to the permanence of colonizatory processes that occur by rescuing ethnocentric models of historical and literary references. To do so, we will use a bibliography which enables us to follow the course of the historical novel genre from its European origins until it became the high critical hybrid genre that currently is written in Latin America